The Use of Crossword Puzzles as the Way to Increase Student’s Vocabulary Mastery at SMA Tamansiswa Binjai - Imam Fahmi Fachrozi; Rahmawati Rahmawati; Mustiara Ayu Andini; Elisa Mutiara Tampubolon; Evelyn Athalia Br Tarigan (Linguistic, English Education and Art (LEEA) Journal, 2021)
The aim of the researcher was to find a technique that could increase the students’s vocabulary. To find out whether interactive method by applying crossword puzzle can improve students’ vocabulary. The researchers gives the students pretest and post test. The researcher use two cycles in this research.We can see that in the first cycle the number of students who got a score of 75 was 6.6% andin the second cycle the number of students who got a score of 75 was 76.6%. This technique add insight to the student’s mastery of the English vocabulary and also it will not make the classes to be boring but also fun. Keywords: Class Action Research, Vocabulary,Crossword Puzzle.